2004
DOI: 10.3748/wjg.v11.i3.429
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of heat shock protein 70 and glucose-regulated protein 94 in human esophageal carcinoma

Abstract: AIM:To investigate the expression and significance of heat shock protein 70 (HSP70) and glucose-regulated protein 94 (grp94) in human esophageal carcinoma and adjacent normal tissues. METHODS:The expression of HSP70 and grp94 in 78 human esophageal cancer and adjacent normal tissues was studied by immunohistochemistry and pathology photograph analysis. RESULTS:Both esophageal cancer and adjacent normal tissues could express HSP70 and grp94. Of the 78 cases of esophageal carcinoma, 95.0%(72/78) showed positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(23 reference statements)
3
14
1
Order By: Relevance
“…In support of this hypothesis, imunohistochemical study on prostate tissue samples showed that GRP94 expression was reduced in prostate cancer when compared with benign prostate tissue. This result is supported by one previous study on esophageal squamous cell carcinoma tissues [28], although the opposite has been found in several other tumor types, indicating a possible tissue specificity for this effect [28,29,[49][50][51]. Additionally, our results demonstrated a trend for correlation between low GRP94 expression and high Gleason score, which in turn is correlated with presence of elevated levels of CTC, further supporting our hypothesis that GRP94 suppression correlates with CTC formation and metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…In support of this hypothesis, imunohistochemical study on prostate tissue samples showed that GRP94 expression was reduced in prostate cancer when compared with benign prostate tissue. This result is supported by one previous study on esophageal squamous cell carcinoma tissues [28], although the opposite has been found in several other tumor types, indicating a possible tissue specificity for this effect [28,29,[49][50][51]. Additionally, our results demonstrated a trend for correlation between low GRP94 expression and high Gleason score, which in turn is correlated with presence of elevated levels of CTC, further supporting our hypothesis that GRP94 suppression correlates with CTC formation and metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is contradictory to several reports in the literature showing increased GRP94 expression in a variety of malignant tumors or cancer cell lines, such as breast (23), oral (24), lung (25), gastric (26), esophageal (27) and colonic carcinomas (28). Using immunohistochemistry we observed that GRP94 was absent or weakly present in ductal cells but strongly present in acinar cells in chronic pancreatitis and normal pancreatic tissues.…”
Section: Discussioncontrasting
confidence: 56%
“…Grp94, also known as gp96, is the ER-resident member of the Hsp90 family constitutively expressed in virtually all cell types (Van et al, 1989) and the most abundant ER chaperon protein showing high homology (50%) to cytosolic counterpart Hsp90 (Sorger and Pelham, 1987). Increased expression of Grp94 both at the mRNA and protein levels also has been reported in several types of human cancers, such as oesophageal cancer (Wang et al, 2005b), lung cancer (Wang et al, 2005a), breast cancer (Gazit et al, 1999), liver cancer (Lim et al, 2005), and colon cancer (Wang et al, 2005c). We hypothesised that Grp94 also has potential as an emerging therapeutic target of interest for the treatment of oral cancer.…”
Section: Discussionmentioning
confidence: 99%